Degradation of Layered Oxide Cathode in a Sodium Battery: A Detailed Investigation by X‐Ray Tomography at the Nanoscale. Issue 10 (21st August 2021) - DiLecce, Daniele; Marangon, Vittorio; Isaacs, Mark; Palgrave, Robert; Shearing, Paul R.; Hassoun, Jusef
Abstract: The degradation mechanism in a sodium cell of a layered Na0.48 Al0.03 Co0.18 Ni0.18 Mn0.47 O2 (NCAM) cathode with P3/P2 structure is investigated by revealing the changes in microstructure and composition upon cycling. The work aims to rationalize the gradual performance decay and the alteration of the electrochemical response in terms of polarization, voltage signature, and capacity loss. Spatial reconstructions of the electrode by X‐ray computed tomography at the nanoscale supported by quantitative and qualitative analyses show fractures and deformations in the cycled layered metal‐oxide particles, as well as inorganic side compounds deposited on the material. These irreversible morphological modifications reflect structural heterogeneities across the cathode particles due to formation of various domains with different Na + intercalation degrees. Besides, X‐ray photoelectron spectroscopy data suggest that the latter inorganic species in the cycled electrode are mainly composed of NaF, Na2 O, and NaCO3 formed by parasitic electrolyte decomposition. The precipitation of these insulating compounds at the electrode/electrolyte interphase and the related structural stresses induced in the material lead to a decrease in cathode particle size and partial loss of electrochemical activity. The retention of the NCAM phase after cycling suggests that electrolyte upgrade may improve the performance of the cathode to achieve practical application for sustainable energy storage. Abstract : A sodium layered oxide cathode is observed with relevant detail using high‐resolution X‐ray computed tomography to disclose the reasons for capacity fade upon long‐term cycling in the battery, and additional findings are given by X‐ray photoelectron spectroscopy.